Vorstellung und Evaluation des haptisch-visuellen, ohrchirurgischen Trainingssystems „HaptiVisT“ - Sorge, Martin; Eixelberger, Thomas; Dietz, Andreas; Simon, Martina; Wittenberg, Thomas; Katzky, Uwe; Perret, Jérôme; Hofer, Mathias; Pirlich, Markus (Laryngo-Rhino-Otologie, 2021)
Background Operations on the temporal bone are a special challenge for ENT surgeons. The aim of the BMBF-funded project was to develop a realistic training system for ear operations in the form of a serious game. Methods The presented prototype of the HaptiVisT system functions as a training system for ear surgeries with visual feedback through a glasses-free 3D monitor and feedback by means of a haptic arm simulating the drill. A variety of training options is guaranteed by three available surgical procedures (antrotomy, mastoidectomy, posterior tympanotomy). A weighted point system enables the measurability of the training success. Following the technical development of the prototype, a prospective evaluation was carried out by eight ENT physicians and four students regarding learning content and user experience. A standardized questionnaire was used (ordinal scale: 1=very good to 5=very bad). Results Regarding the learning content, the aspects strengthening anatomy (mean=1.58), training hand-eye coordination (1.67), transferability into practice (1.83), usefulness for practice (1.33) yielded good to very good scores. User experience also showed good results for the aspects realism (2.29), interaction of haptics and optics (2.33) and immersion in the training system (1.89). The motivation factor was very high for all test subjects (1.2). Conclusions The training system for ear surgeries HaptiVisT offers the possibility of immersive training. Integration into the daily clinical routine and in particular into the medical training to become an ENT specialist therefore seems to make sense.
Created from Fastlane, Scopus look-up
Keywords: ear surgery; erfahrbares Lernen; haptisch-visuelles Trainingssystem; HaptiVisT; Ohrchirurgie; serious game; virtual surgery training; virtuelles chirurgisches Training